An Activity-Based Proteomics Approach for Identifying Ajoene's S-thiolation Protein Targets in Blood and Cancer Cells - Kusza, Daniel Andreas (Department of Chemistry, 2022)
Garlic has been used as a medicinal plant since ancient times and is well-documented to produce several organosulfur compounds (OSCs) that show promising chemopreventative and therapeutic properties. The vinyl disulfide sulfoxide garlic rearrangement product, ajoene, is one of the phytochemicals in garlic that possesses a broad spectrum of biological activities against a variety of cancers both in vitro and in vivo. Our group's previous investigations into ajoene's cytotoxicity have shown that it modifies proteins by S-thioallylating redox-sensitive cysteine residues through a thioldisulfide exchange reaction. Further investigations into this exchange have been the primary aim of this PhD thesis using a biotinylation protocol for trapping out the said protein targets of ajoene to link them to anticancer signalling pathways. The thesis begins in Chapter One with an overview of the chemopreventative and antitumour activity of OSCs from garlic in which a particular emphasis is placed on OSC structure and mechanistic aspects of their cancer biology. Chapter Two discusses the various aspects of ajoene as the target natural product of the thesis. These include its biosynthesis and synthesis, in both native form and as derivatives, for SAR studies, for which a UCT synthesis is described. Mechanistic aspects of ajoene's cytotoxicity towards cancer cells in terms of S-thioallylation via disulfide exchange are then discussed at length. Of crucial importance for the chemical biology studies to follow was the conclusion that S-thioallylation by ajoene is regioselective at the vinyl sulfur, as well as effectively irreversible with suitably reactive cysteine thiol groups. Chapter Three presents an in-depth Chapter on the metabolism and pharmacokinetic properties of ajoene and selected derivatives in a murine xenograft model for human oesophageal cancer (WHCO1). This concluded, disappointingly, that no significant differences in terms of tumour volume, mass and growth rate were observed compared to an untreated control. A follow-up study using a small library of eight ajoene derivatives varying ajoene's different functional groups in a blood stability study, revealed a proportional relationship between the in vitro half-life in blood and the IC50 value for WHCO1 cancer cells. This led to mass spectrometry studies showing that ajoene Sthioallylates the βCys-93 residues in haemoglobin, a chemical modification that most likely explains both ajoene's blood instability and its lack of antitumour activity in vivo. Chapter Four describes the organic synthesis and characterisation of four biotin-ajoene chemical biology probes for chemical biology investigation of S-thiolation in which the background theory of activity-based protein profiling and biotin affinity purification is presented. In the synthesis of these probes, chemical stability emerged as a major stumbling block. Gratifyingly, after several trials, the fourth probe designed and constructed, using a simplified tether involving a convergent “Click”-strategy, turned out to be chemically stable. Subsequent biological validation studies confirmed that the probe retained cytotoxicity against cancer cell lines in vitro (human epithelial mammary gland adenocarcinoma cancer cells (MDA-MB-231) and WHCO1) and shared the same compound–target interaction as its parent ajoene; namely, the regioselective S-thiolation of cellular proteins. Chapter Five constitutes a proteomics study into ajoene's primary protein targets in the MDA-MB-231 cell line using our biotin-ajoene probe. Streptavidin-coated magnetic beads in conjunction with an affinity purification mass spectrometry protocol allowed the isolation and identification of 633 protein targets for ajoene in the MDA-MB-231 proteome. Pathway analyses revealed that ajoene interacts with several targets involved in the control of cell cycles (G2/M cell cycle checkpoint), energy metabolism (glycolysis and pentose phosphate pathway) and the regulation of protein metabolism (translation, folding, quality control and degradation), which supports previously reported cytotoxic modes of action for ajoene against MDA-MB-231 cancer cells. Importantly, we have validated that ajoene S-thioallylates glutathione S-transferase (GSTP1), which is a known cancer-therapy target in breast cancer. Overall, this study complements findings on the cancer-cell protein targets of allicin from crushed garlic, by identifying proteins regulating apoptotic and antiproliferative signalling pathways. These findings support the hypothesis that the anticancer activity of ajoene is due to its S-thioallylation of proteins essential to cellular functions. The thesis concludes with comprehensive experimental and reference sections.